A critique of the racialised and neo-colonial politics of listening: Ousmane Sembene's La Noire de … (1966). Issue 2 (3rd April 2021) - Knox, Katelyn E.
ABSTRACT: This article considers one of the most canonical films in Francophone African cinema, Ousmane Sembene's La Noire de… (1966), through the lens of listening to reveal new dimensions of the film's neo-colonial critique. Applying concepts developed in inquiries into racialised politics of listening in the United States context, this article shows how the film both exposes and critiques Diouana's employers' privilege to selectively decide what sound matters. Reading the film through the lens of listening also adds new resonance to the mask, and, in turn, the sequences in which it plays a major role. Namely, exploring the mask's larger cultural significance – it is an initiation mask associated with the sulaw class of the Bamana korè society – recasts, in part, Diouana's employment as her own initiation into global political orders, whose politics of listening do not match her expectations. Through her suicide, Diouana begins to dismantle the racialised politics to which she is subjected in France and forces, if only temporarily, Monsieur to experience life outside his own comfortable ways of listening. Ultimately, the article contends that the film challenges its audience to consider its own ways of listening and, perhaps, the politics of listening surrounding the film itself.